Alpha and beta cell evaluation in patients with thalassaemia intermedia and iron overload. Issue 721 (November 1985) - De Sanctis, V.; Gamberini, M. R.; Borgatti, L.; Atti, G.; Vullo, C.; Bagni, B.
Abstract : Insulin and glucagon secretion were studied during an oral glucose tolerance test and arginine infusion in 11 patients with thalassaemia intermedia, who showed laboratory evidence of iron overload. Mean blood glucose concentrations in patients with thalassaemia intermedia were significantly higher than normal and 3 of 11 patients had impaired glucose tolerance. The principal abnormality appears to be a deficiency in insulin and glucagon from the pancreas in response to oral glucose tolerance and arginine stimulation tests. Several factors, such as iron overload, chronic hypoxia, zinc deficiency and increased catecholamine production secondary to anaemia, might play a part in the pathogenesis of these abnormalities. Each of these factors affect individual cases to a varied degree. Our data emphasize the mildness of carbohydrate defect as compared to the degree of insulinopenia and indicate the necessity for prescribing measures which prevent excessive iron deposition and improve iron excretion in thalassaemic patients with iron overload.